Gerald's game - King, Stephen, 1947-; Crouse, Lindsay; HighBridge Audio (Firm) ([St. Paul, Minn.] : HighBridge Audio, 2008)
Gerald Burlingame and his wife Jessie have been married for twenty years and together have always been into kinky sex. But one night during a handcuffed midnight rendezvous Jessie finds herself trapped under her husband's corpse. With Jessie's troubling past she must find a way out before the police arrive and things really start to get out of hand.
Compact discs.
Title from container.
Duration: 13:30:00.
Read by Lindsay Crouse.
Keywords: Married people -- Sexual behavior -- Fiction; Fear -- Fiction; Audiobooks; Horror fiction